Learning the genetics concepts through project activities using Drosophila melanogaster: A qualitative descriptive study - Fauzi, Ahmad; Ramadani, Shefa Dwijayanti (Jurnal Pendidikan Biologi Indonesia, 2017)
Genetics is one of difficult subject for many undergraduate students majoring biology. Authentic-based research is one of learning activity believed could overcome the situation. One of Genetics course that facilitating the students to conduct authentic-based research is Genetics course in Faculty of Mathematics and Natural Science, State University of Malang. The aim of this study was to describe the project research activities in Genetics course, especially the authentic-based research that utilize Drosophila melanogaster. The present study is qualitative descriptive with the object of this study is project activities in Genetics course. In this institution, the Genetics course is divided into Genetics I (taken by fourth semester students) and Genetics II (taken by fourth semester students). Data collection was conducted from 2014 until 2017 using open ended interviews and observation. An analytical strategy from Miles & Huberman was used to analyze the data. D. melanogaster was used as model organism in several Genetics projects. The genetics project was conducted from first until sixteenth week. In the project activities, the students get some flies strains, observe its phenotypes, design their research project, collect the data, analyze the data , prepare the report, ant present their project result.In this activities, students could practice to be a real researcher. Based on interviews with some students and observations during the presentation of the project reports,it can be seen that through this learning activities the students achieved better understanding about many genetics concepts. Moreover, several students have an opportunity to present their research results in International Conference events.